Impact of Cognitive Demand during Sustained Near Tasks in Children and Adults. Issue 3 (March 2018) - Roberts, Tawna L.; Manny, Ruth E.; Benoit, Julia S.; Anderson, Heather A.
Abstract : SIGNIFICANCE: These results demonstrate that accommodation in children is more accurate and less variable when performing a sustained near task with increased cognitive demand. In addition, children with increased uncorrected hyperopia have less stable accommodative responses, which may have visual implications during sustained near tasks. PURPOSE: This study investigated accommodative accuracy (lag) and variability during sustained viewing for passive and active tasks in children and adults with emmetropia and uncorrected hyperopia. METHODS: Lag and variability (root mean square [RMS] and low-frequency component) were measured in 54 children aged 3 to younger than 10 years with mean spherical equivalent of +1.31 ± 1.05 diopters (D) (range, −0.37 to +4.58 D) and 8 adults aged 22 to 32 years with mean spherical equivalent +0.65 ± 0.62 D (range, −0.13 to +1.15 D). Subjects viewed 20/50 stimuli at 33 cm during both a 10-minute passive and active task. Group 1 (<6 years or nonreaders) viewed shapes; group 2 (≥6 years and reading) and adults read passages. RESULTS: Groups 1 and 2 had larger lags, RMS, and low-frequency component for passive versus active tasks ( P < .001). Lag and RMS did not differ between tasks in adults ( P > .05), but low-frequency component was larger during passive viewing ( P = .04). Group 1 had significantly higher RMS and low-frequency component than group 2 and the adults in the passive condition had greater low-frequency component in the active condition. In children, hyperopia was independently associated with RMS and low-frequency component under passive (RMS 95% confidence interval [CI], 0.04 to 0.15; low-frequency component 95% CI, 0.00011 to 0.00065) and active (RMS 95% CI, 0.001 to 0.06; 95% CI, 0.000014 to 0.00023) viewing. CONCLUSIONS: Accommodation is more accurate and less variable when children are engaged in the task. Children also have more variable accommodation than adults. In addition, children with greater hyperopia have more variable accommodation during sustained near tasks.